Entrepreneurship: Tenacity, Future Self-Continuity, and Inter-Temporal Risky Choice - Zeng, Xueyun; Ouyang, Yuting (Frontiers in Psychology, 2020)
This study examines entrepreneurship. It focuses on the effect of tenacity and future self-continuity on inter-temporal risky choice in entrepreneurial context. A total of 129 Chinese undergraduates participated in this survey. The results formulate that tenacity positively correlates with the risky choices and inter-temporal risky choices, in which endurance, commitment and challenge play a major role in the impact of tenacity on entrepreneurial choice. Meanwhile, future self-continuity predicts the risk-return of the subjects. Higher future self-continuity corresponds to higher expected inter-temporal risk-return. Furthermore, the multivariable regression analysis shows that there is a reciprocal effect when tenacity and future self-continuity work together on subjects’ inter-temporal risky decision-making. Future self-continuity slightly mitigates both the pursuit of risky-return and the tolerance of time delay for the subjects with high tenacity. That implies their worthwhile goal is to seek a smooth income rather than to pursue an extreme high risk-return. These findings extend the research on personality, choice and entrepreneurship as well as providing a guiding significance to the start-up.